Phänomenologie als Urwissenschaft und neue “Metaphysik der Metaphysik”. Die systematische Genealogie von Heideggers philosophischen Anfängen - Seubert, Harald (Bollettino Filosofico, 2020)
This essay reconstructs the inner consistency and posthumously reconstructable and manageable systematicity of Heidegger’s independent phenomenological beginnings immediately after World War I. Heidegger shares with Husserl the understanding of phenomenology as a primordial science, he specifies this from the logical orientation on the “question of objectivity” and in the “formal display”, which goes back to nominalism. Against this philosophical background Heidegger contradicts the reduction of philosophy on the one hand to scientism and historicism, and on the other hand to worldview. The primary-scientific-philosophical claim rather remains valid, where in first attempts the categories of existence are outlined in a phenomenology of the living world reference of existence, where the counterpoint of “ruin” and “ethos” is sketched as an interpretation of residence, and where ideological and religious approaches to the world are examined phenomenologically. It is the thesis of the treatise that Heidegger thereby already sets the impulse that goes beyond the ‘fundamental ontology’ in Being and Time and aims at a “metaphysics of metaphysics” in the Kantian sense. Keywords: Existence, Heidegger, Husserl, Metaphysics, Phenomenology